DIETARY PATTERN AND NUTRIENT INTAKE OF OVERWEIGHT AND NORMAL WEIGHT ADOLESCENT GIRLS – A CROSS-SECTIONAL STUDY. - Parveen N, Asma; John, Sheila; Monica, Sarah Jane (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the study was to evaluate and compare the dietary pattern and nutrient intake of overweight and normal weight adolescent girls. Methods: A cross-sectional study was conducted among 200 adolescent girls aged 18â€“22 years. Information regarding demographic profile and the dietary pattern was obtained using a questionnaire. Anthropometric measurements such as height, body weight, and waist circumference were measured and body fat percentage was estimated. Nutrient intake was calculated using 3 days dietary recall method. In addition, a nutrition education program was conducted to create an impact on the dietary habits. Results: The study showed that majority of the subjects in both the groups was non-vegetarians. With regards to meal skipping, 76% of the overweight girls had the habit of skipping meal and breakfast was the most common meal that was skipped. There was a significant difference in the anthropometric indices and nutrient intake between normal and overweight subjects. Subjects in both the groups were fond of eating junk foods followed by inadequate intake of fruits. Nutrition education program helped them to change their dietary habits. Conclusion: Providing nutrition education to adolescents is essential as it creates an impact on the eating habits by modifying their dietary pattern and creating awareness about the ill health effects of junk food consumption.